Effect of Alzheimer's disease‐related β‐amyloid peptide conformations in transgenic mouse models of β‐amyloidosis: Development of new models and analysis methods/seeding and spreading of proteinopathies. (7th December 2020) - Célestine, Marina; Jacquier‐Sarlin, Muriel; Borel, Eve; Herard, Anne‐Sophie; Buisson, Alain; Dhenain, Marc
Abstract: Background: Alzheimer's disease (AD) brain dysfunctions are not exclusively related to amyloid plaques occurence, but are thought to start much earlier, presumably due to soluble pathological forms of b‐amyloid peptide (Aβ). Indeed Aβ oligomers induce synaptic dysfunctions that cause cognitive decline, exacerbate tau pathology[1] and influence neuronal networks[2]. Although mutation‐induced phenotypes are identified in AD patients, the in vivo effects of different Aβ variants are poorly understood. Here we characterized the effects of different Aβ variants in a transgenic mouse model to provide deeper insight of transconformational processes and the subsequent alterations. Deciphering Ab profiles would help in developing new diagnostic and therapeutic approaches. Method: We developed well‐characterized amyloid variants: Aβ1‐42, Aβ bearing the icelandic mutation (A2T), Aβ bearing the Osaka mutation (E22D[1]) and Aβ bearing the mutation F19S/L34P. First, these variants were overexpressed in cortical neuron cultures. Then, two‐month‐old APP/PS1dE9 mice were inoculated with these variants in the dentate gyrus (n = 5/per group). We assessed Aβ oligomerization profiles, cerebral amyloid load and synaptic health in neuron and mouse (4 months post‐inoculation) models by biochemistry and histology. Result: The different amyloid forms exhibit distinct aggregation profiles and synaptotoxicity in vitro (Figure 1). They did not have the same effect on mouse survival. Osaka‐Aβ induced the highest mortality. Then, we focused on the local reorganization of amyloid. Osaka‐Aβ led to increased 6‐mer and 12‐mer amyloid forms at inoculation site (Figure 2) but also at distance in the cortex. This suggests that Aβ variants differently modulate Aβ metabolism and aggregation. Amyloid plaque assessment showed an Osaka‐Aβ‐induced increase in amyloid load in the hippocampus (Figure 3) and its connected regions. Conclusion: A single inoculation of different Aβ variants in APP/PS1dE9 mice expressing wild‐type Aβ is sufficient to differentially modulate Aβ metabolism, amyloid load and mouse mortality. This suggests that Aβ variants differentially interact with the biochemical/biophysical cerebral environments to differentially induce toxic downstream events that are crucial for better AD physiopathology understanding. References: (1) Delacourte et al., Experimental Gerontology, 2002. (2) Bero et al., Journal of Neuroscience, 2012. (3) Tomiyama et al., Ann Neurol, 2008.